2019
DOI: 10.1002/jcla.23008
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of clinical characteristics of 92 patients with paroxysmal nocturnal hemoglobinuria: A single institution experience in China

Abstract: Objectives We performed a retrospective analysis to investigate the clinical characteristics and therapeutic strategies of Chinese paroxysmal nocturnal hemoglobinuria (PNH) patients, and assessed the efficacy and safety of glucocorticoid in PNH patients. Methods The clinical data of 92 PNH cases in our hospital were analyzed, including clinical manifestation, laboratory examination, treatment efficacy, and survival. Results The main clinical manifestations of these patients included hemoglobinuria, anemia, fat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
9
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 32 publications
1
9
0
1
Order By: Relevance
“…Glucocorticoids are still effective drugs for reducing hemolysis to control PNH. After years of clinical progress, the current use of glucocorticoids and hematopoietic therapy has allowed the remission rate of the disease reach more than 60%, but nearly 40% of patients are not sensitive to this treatment 16,17 . Even in patients who achieve remission after treatment, there is still more than a 10% possibility of relapse 18 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Glucocorticoids are still effective drugs for reducing hemolysis to control PNH. After years of clinical progress, the current use of glucocorticoids and hematopoietic therapy has allowed the remission rate of the disease reach more than 60%, but nearly 40% of patients are not sensitive to this treatment 16,17 . Even in patients who achieve remission after treatment, there is still more than a 10% possibility of relapse 18 .…”
Section: Discussionmentioning
confidence: 99%
“…After years of clinical progress, the current use of glucocorticoids and hematopoietic therapy has allowed the remission rate of the disease reach more than 60%, but nearly 40% of patients are not sensitive to this treatment. 16 , 17 Even in patients who achieve remission after treatment, there is still more than a 10% possibility of relapse. 18 At the end of the 1970s, Soviet scholars reported that cyclophosphamide or 6‐mercaptopurine achieved certain effects in the treatment of PNH.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of treatment, complement inhibition therapy in the form of eculizumab has improved treatment prospects for PNH patients in developed countries[ 6 , 7 ]. However, high costs and access difficulties have limited the utilization of eculizumab in China, and steroid therapy is still the preferred treatment to control hemolytic attacks in PNH patients[ 8 ]. In this case, the patient's hyperbilirubinemia was relieved after the administration of methylprednisolone, and the treatment achieved relatively favorable outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Glucocorticoids are still effective drugs for reducing hemolysis to control PNH. After years of clinical progress, the current use of glucocorticoids and hematopoietic therapy has allowed the remission rate of the disease reach more than 60%, but nearly 40% of patients are not sensitive to this treatment [16,17]. Even in patients who achieve remission after treatment, there is still more than a 10% possibility of relapse [18].…”
Section: Discussionmentioning
confidence: 99%